PENDAMPINGAN REMAJA PUTRI TENTANG KESEHATAN REPRODUKSI DALAM MENGURANGI TINGKAT STRES PADA SAAT KEPUTIHAN DI PESANTREN ALMUQRI PARENDUAN - Dian Permatasari; Emdat Suprayitno (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2021)
Leucorrhoea (fluorine Albus / vaginal discharge) is an excessive discharge of non-blood from the female genitals (vagina). Leucorrhoea is often considered normal by the community so that it is not handled properly, but this vaginal discharge could indicate disease. Physiological leucorrhoea is found in the condition before and after menstruation, sexual stimulation, pregnancy, ovulation, and emotional stress. The mentoring method used is to provide health education on reproductive health. The results of the implementation of health education were Al Muqri Parenduan Islamic boarding school students were active, enthusiastic in participating in activities, and active in discussing reproductive health. Activity participants can understand the level of stress on vaginal discharge and can explain again what has been conveyed.